2019
DOI: 10.1021/acsami.8b22579
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidics-Prepared Uniform Conjugated Polymer Nanoparticles for Photo-Triggered Immune Microenvironment Modulation and Cancer Therapy

Abstract: Photothermal therapy (PTT) has shown great promise to spatiotemporally ablate cancer cells, and further understanding of the immune system response to PTT treatment would contribute to improvement in therapeutic outcomes. Herein, we utilize microfluidic technology to prepare biocompatible conjugated polymer nanoparticles (CP NPs) as PTT agents and assess the immune response triggered by CP-based PTT treatment in vitro and in vivo. Through careful control of the antisolvent, CP NPs with a uniform diameter of 52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 53 publications
1
48
1
Order By: Relevance
“…Over the past few decades, nanoprecipitation has revolutionized the synthesis of lipid and polymer-based nanoparticles (NPs). [1][2][3][4][5][6][7][8][9] It is considered to be a fast, straightforward and reproducible method to synthesize small and monodisperse NPs with size ranges of 20 to 300 nm and polydispersity indices (PDI) of less than 0.2. [9][10][11] To date, the nanoprecipitation method has been used for the synthesis of many drug-loaded NPs and dye-loaded NPs composed of biocompatible and biodegradable polymers, such as poly(lactide-co-glycolic acid) (PLGA), poly(lactide-coglycolide)-b-poly(ethylene glycol) (PLGA-PEG), poly(ethylene glycol)b-poly(e-caprolactone) (PEG-b-PCL) and 1,2-distearoyl-sn-glycero-3phosphoethanolamine-polyethylene glycol (DSPE-mPEG).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, nanoprecipitation has revolutionized the synthesis of lipid and polymer-based nanoparticles (NPs). [1][2][3][4][5][6][7][8][9] It is considered to be a fast, straightforward and reproducible method to synthesize small and monodisperse NPs with size ranges of 20 to 300 nm and polydispersity indices (PDI) of less than 0.2. [9][10][11] To date, the nanoprecipitation method has been used for the synthesis of many drug-loaded NPs and dye-loaded NPs composed of biocompatible and biodegradable polymers, such as poly(lactide-co-glycolic acid) (PLGA), poly(lactide-coglycolide)-b-poly(ethylene glycol) (PLGA-PEG), poly(ethylene glycol)b-poly(e-caprolactone) (PEG-b-PCL) and 1,2-distearoyl-sn-glycero-3phosphoethanolamine-polyethylene glycol (DSPE-mPEG).…”
Section: Introductionmentioning
confidence: 99%
“…The results confirmed that PB‐Ft NPs have the capability to inhibit cellular growth of the murine breast cancer cells (4T1) effectively [81]. Similarly, another study utilised microfluidic technology to synthesise biocompatible conjugated polymer NPs (CP NPs) as PTT agents and found out that CP NPs display high photothermal conversion efficacy, inducing effective breast cancer cell death under 808 nm NIR laser illumination [82].…”
Section: Application Of Hybrid Nps Against Different Type Of Cancersmentioning
confidence: 73%
“…Same as our previous study, we have fabricated microfluidic coaxial glass capillary mixer and synthesized CP NPs at flow rate of 34 ml/min (Re 320) ( Supplementary Fig. S1 and Supplementary Equation S3) 29,30 . At Re 320, we obtained the CP NPs with an average diameter of 48 nm and polydispersity of 0.14.…”
Section: Methodsmentioning
confidence: 99%
“…This is also known as solvent displacement based method where the polymers are dissolved in a water miscible organic solvent, and rapid mixing of solvent into anti-solvent (water) results in the spontaneous formation of nanoparticles. Nanoprecipitation through microfluidic glass capillary mixer has gained some attentions as it exhibits tunable physiochemical properties and efficient mixing 28 , 29 . Due to high surface area to volume interaction, microfluidic mixers provide the benefits of enhanced and uniform mixing during NP fabrication.…”
Section: Methodsmentioning
confidence: 99%